2022
DOI: 10.3389/fimmu.2022.923727
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metabolic and transcriptional responses by the thyroid hormone in cellular models of murine macrophages

Abstract: Oncogene-immortalized bone marrow-derived macrophages are considered to be a good model for the study of immune cell functions, but the factors required for their survival and proliferation are still unknown. Although the effect of the thyroid hormones on global metabolic and transcriptional responses in macrophages has not yet been examined, there is increasing evidence that they could modulate macrophage functions. We show here that the thyroid hormone T3 is an absolute requirement for the growth of immortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
1
1
Order By: Relevance
“…This is in contrast with our data, as we found decreased proinflammatory markers in M1 BMDMs without T3. It is important to note, however, that in this study BMDMs were only stimulated with IFN-y for 2 h, whereas in the current report BMDMs were stimulated with a combination of LPS and IFN-y for 24 h [27].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This is in contrast with our data, as we found decreased proinflammatory markers in M1 BMDMs without T3. It is important to note, however, that in this study BMDMs were only stimulated with IFN-y for 2 h, whereas in the current report BMDMs were stimulated with a combination of LPS and IFN-y for 24 h [27].…”
Section: Discussioncontrasting
confidence: 66%
“…Another study also reported on decreased proinflammatory markers in T3-deficient macrophages, although IL-6 was unaffected in different macrophage cell lines and primary peritoneal macrophages [20]. In a study where BMDMs were stimulated with IFN-y, which elicits a proinflammatory response, phosphorylated STAT-1 and JAK-2 were more abundant in T3depleted BMDMs [27]. The JAK/STAT-1 pathway is an inducer of the M1 phenotype [28,29].…”
Section: Discussionmentioning
confidence: 94%